Rare earth microalloyed ultrathin copper foil prepared based on magnetron sputtering

The preparation of rare earth microalloyed extremely thin copper foil through magnetron sputtering technology solves the problems of poor uniformity and stability of copper foil, and realizes copper foil with excellent performance, which is suitable for high-performance electronic equipment.

CN119913471APending Publication Date: 2025-05-02SHANDONG QIYE ELECTRONIC MATERIALS CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510164245.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-14
Publication Date
2025-05-02

AI Technical Summary

Technical Problem

The uniformity and stability of existing copper foils are poor, making it difficult to meet the needs of high-performance electronic equipment.

Method used

Rare earth microalloyed extremely thin copper foil is prepared by magnetron sputtering technology. The oil stains and impurities on the surface of the metal matrix are removed by pretreatment and polishing, the parameters during the sputtering process are accurately controlled, and the annealing process is performed to improve the density and adhesion of the copper foil.

Benefits of technology

Significantly improve the conductivity, strength, elongation and wear resistance of copper foil, improve its overall performance, and enhance tensile strength and peel strength.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a rare earth microalloyed ultrathin copper foil prepared based on magnetron sputtering, and belongs to the technical field of copper foil manufacturing. According to the rare earth microalloyed ultrathin copper foil prepared based on magnetron sputtering, a metal matrix is put into an ultrasonic cleaning machine to be cleaned, the metal matrix continues to be polished, the magnetron sputtering technology is adopted for deposition, rare earth elements lanthanum and cerium are added, and finally annealing treatment is conducted, so that the rare earth microalloyed ultrathin copper foil is prepared. The rare earth microalloyed ultrathin copper foil prepared on the basis of magnetron sputtering has excellent tensile strength and peel strength.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of copper foil manufacturing, and in particular relates to a rare earth micro-alloyed ultra-thin copper foil prepared based on magnetron sputtering. Background Art

[0002] Copper foil is a very thin, continuous metal foil whose main component is copper. As an important conductive material, copper foil is widely used in electronics, communications, aerospace, automobiles, construction and other fields, especially in printed circuit boards (PCBs), flexible circuit boards (FPCs) and lithium-ion batteries.

[0003] With the rapid development of new energy vehicles and the demand for increased energy density of power batteries, copper foil is developing towards lighter and thinner. Thinner copper foil helps reduce the cost of battery collectors and improve the overall energy density of batteries. In order to meet the needs of high-performance electronic devices, material scientists are constantly committed to developing thinner, more conductive, and more stable copper foil. Therefore, the present invention develops a rare earth micro-alloyed ultra-thin copper foil prepared by magnetron sputtering to solve the technical problems of poor uniformity and stability of copper foil in the prior art. Summary of the invention

[0004] The purpose of the present invention is to provide a rare earth micro-alloyed ultra-thin copper foil prepared based on magnetron sputtering, which is used to solve the technical problems of poor uniformity and stability of copper foil in the prior art.

[0005] In order to achieve the above object, the present invention adopts the following technical solutions: A rare earth micro-alloyed ultra-thin copper foil prepared by magnetron sputtering comprises the following steps: (1) Pretreatment: Place the metal substrate in an ultrasonic cleaning machine and immerse it in an acetone solution for cleaning. After cleaning, rinse it with deionized water and dry it in an oven to obtain a clean metal substrate. (2) Polishing: Place the clean metal substrate in the polishing liquid, set the polishing time and polishing temperature, and after completion, rinse it with deionized water and place it in an oven to dry to obtain a polished metal substrate; (3) Prepare for sputtering: start the vacuum pump, evacuate the sputtering chamber to the working vacuum degree, introduce argon gas into the sputtering chamber, install the rare earth microalloy copper target, set the power of the sputtering power supply, adjust the distance between the target and the substrate, and set the pre-sputtering time; (4) Sputtering: Start the sputtering power supply to carry out deposition. After completion, a deposited metal substrate is obtained. (5) Annealing: The deposited metal substrate is annealed under argon gas to obtain a rare earth micro-alloyed ultra-thin copper foil prepared by magnetron sputtering.

[0006] Furthermore, in step (1), the metal substrate is one of stainless steel strip, aluminum foil and rolled copper foil, the cleaning time is 10-15 minutes, the oven drying temperature is 60-80°C, and the drying time is 30-60 minutes; in step (2), when the metal substrate is stainless steel strip, the polishing liquid is a mixture of nitric acid and phosphoric acid, the concentration of nitric acid is 10-15%, the concentration of phosphoric acid is 10-15%, the volume ratio of nitric acid to phosphoric acid is 1:1, the polishing time is 5-10 minutes, and the polishing temperature is 50-60°C; when the metal substrate is aluminum foil, the polishing liquid is a mixture of hydrofluoric acid and nitric acid, the hydrofluoric acid is 1:1. The concentration of the acid is 5-10%, the concentration of the nitric acid is 5-10%, the volume ratio of hydrofluoric acid to nitric acid is 1:2, the polishing time is 3-5 minutes, and the polishing temperature is 30-40°C; when the metal substrate is a rolled copper foil, the polishing liquid is a mixture of sulfuric acid and hydrogen peroxide, the concentration of the sulfuric acid is 15-20%, the concentration of the hydrogen peroxide is 15-20%, the volume ratio of hydrofluoric acid to nitric acid is 1:1, the polishing time is 2-4 minutes, the polishing temperature is 40-50°C, the oven drying temperature is 60-80°C, and the drying time is 30-60min; the working vacuum degree in step (3) is 10 -6 -10 -9 Pa, the argon gas flow rate is 20-30sccm, the rare earth microalloy copper target contains rare earth elements lanthanum and cerium, the ratio of La to Ce is 3 / 7-6 / 4, the content is 10-1000ppm, the content of other impurities is ≤10ppm, the power of the sputtering power supply is 100-300W, the distance between the target and the substrate is 5-10cm, and the pre-sputtering time is 5-10 minutes; in step (5), the annealing temperature is 200-300°C, the annealing time is 10-30 minutes, and the thickness of the copper foil is 0.5-4.5μm.

[0007] In summary, due to the adoption of the above technical solution, the beneficial effects of the present invention are: 1. The present invention pre-treats and polishes the metal substrate to remove oil stains and impurities on the surface of the metal substrate and further smoothes the substrate surface to reduce surface defects, which is beneficial to the uniform deposition of target atoms in the subsequent sputtering process; moreover, by accurately controlling the working vacuum degree of the sputtering chamber, the flow rate of argon gas, the power of the sputtering power supply, the distance between the target and the substrate, and the pre-sputtering time and other parameters, the stability and controllability of the sputtering process can be ensured, which is beneficial to improving the sputtering rate and the coating quality, thereby obtaining a rare earth micro-alloyed ultra-thin copper foil with excellent performance.

[0008] 2. The present invention uses magnetron sputtering to make electrons run in a spiral shape near the target surface, thereby increasing the probability of electrons colliding with argon gas to generate ions. The generated ions bombard the target material at a high speed under the action of the electric field, sputtering target material atoms, and the atoms are deposited on the substrate to form a dense metal film. Since the sputtered atoms have high energy, it is beneficial to improve the diffusion ability of atoms during deposition, thereby improving the density and adhesion of the copper foil; further, through the microalloying effect of rare earth elements (such as La and Ce), the conductivity, strength, elongation and wear resistance of the copper foil can be significantly improved, the microstructure of the copper foil can be optimized, and defects can be reduced, thereby improving its overall performance; in addition, annealing can eliminate the stress and defects generated during the sputtering process, further improve the conductivity and strength of the copper foil, and annealing under a protective atmosphere can prevent the copper foil from being oxidized or contaminated during the annealing process, thereby obtaining a rare earth microalloyed ultra-thin copper foil with excellent performance. DETAILED DESCRIPTION

[0009] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0010] Embodiment 1: A rare earth micro-alloyed ultra-thin copper foil prepared by magnetron sputtering comprises the following steps: (1) Pretreatment: Place the stainless steel strip in an ultrasonic cleaning machine and immerse it in an acetone solution for cleaning for 10 minutes. After cleaning, rinse it with deionized water and place it in an oven for drying at 60°C for 30 minutes to obtain a clean metal substrate. (2) Polishing: Put the clean metal substrate into the polishing liquid, which is a mixture of nitric acid and phosphoric acid. The concentration of nitric acid is 10%, the concentration of phosphoric acid is 10%, and the volume ratio of nitric acid to phosphoric acid is 1:1. The polishing time is 5 minutes and the polishing temperature is 50°C. After the polishing is completed, rinse with deionized water and put into an oven for drying. The oven drying temperature is 60°C and the drying time is 30 minutes to obtain a polished metal substrate. (3) Prepare for sputtering: Start the vacuum pump and evacuate the sputtering chamber to the working vacuum degree, which is 10 -6 Pa, introduce argon gas into the sputtering chamber, the argon gas flow rate is 20sccm, install a rare earth microalloyed copper target, the rare earth microalloyed copper target contains rare earth elements lanthanum and cerium, the ratio of La to Ce is 3 / 7, the content is 10ppm, and the content of other impurities is ≤10ppm, set the power of the sputtering power supply to 100W, adjust the distance between the target and the substrate to 5cm, and set the pre-sputtering time to 5 minutes; (4) Sputtering: Start the sputtering power supply to carry out deposition. After completion, a deposited metal substrate is obtained. (5) Annealing: The deposited metal substrate is annealed under argon gas at a temperature of 200°C for 10 minutes to obtain a rare earth micro-alloyed ultra-thin copper foil prepared by magnetron sputtering.

[0011] Embodiment 2: A rare earth micro-alloyed ultra-thin copper foil prepared by magnetron sputtering comprises the following steps: (1) Pretreatment: Place the aluminum foil in an ultrasonic cleaning machine and immerse it in an acetone solution for cleaning for 12 minutes. After cleaning, rinse it with deionized water and place it in an oven for drying at 65°C for 40 minutes to obtain a clean metal substrate. (2) Polishing: Place the clean metal substrate into the polishing liquid, which is a mixture of hydrofluoric acid and nitric acid. The concentration of hydrofluoric acid is 6%, the concentration of nitric acid is 6%, and the volume ratio of hydrofluoric acid to nitric acid is 1:2. The polishing time is 3 minutes and the polishing temperature is 30°C. After the polishing is completed, rinse with deionized water and place in an oven for drying. The oven drying temperature is 60°C and the drying time is 30 minutes to obtain a polished metal substrate. (3) Prepare for sputtering: Start the vacuum pump and evacuate the sputtering chamber to the working vacuum degree, which is 10 -6 Pa, introduce argon gas into the sputtering chamber, the argon gas flow rate is 23sccm, install a rare earth microalloyed copper target, the rare earth microalloyed copper target contains rare earth elements lanthanum and cerium, the ratio of La to Ce is 3 / 7, the content is 100ppm, and the content of other impurities is ≤10ppm, set the power of the sputtering power supply to 100W, adjust the distance between the target and the substrate to 7cm, and set the pre-sputtering time to 5 minutes; (4) Sputtering: Start the sputtering power supply to carry out deposition. After completion, a deposited metal substrate is obtained. (5) Annealing: The deposited metal substrate is annealed in argon gas at a temperature of 220°C for 15 minutes to obtain a rare earth micro-alloyed ultra-thin copper foil prepared by magnetron sputtering.

[0012] Embodiment 3: A rare earth micro-alloyed ultra-thin copper foil prepared by magnetron sputtering comprises the following steps: (1) Pretreatment: Place the rolled copper foil in an ultrasonic cleaning machine and immerse it in an acetone solution for 14 minutes. After the cleaning, rinse it with deionized water and place it in an oven for drying at 75°C for 50 minutes to obtain a clean metal substrate. (2) Polishing: Place the clean metal substrate into a polishing solution, which is a mixture of sulfuric acid and hydrogen peroxide. The concentration of sulfuric acid is 17%, the concentration of hydrogen peroxide is 17%, and the volume ratio of hydrofluoric acid to nitric acid is 1:1. The polishing time is 3 minutes and the polishing temperature is 45°C. After the polishing is completed, rinse with deionized water and place in an oven for drying. The oven drying temperature is 70°C and the drying time is 50 minutes to obtain a polished metal substrate. (3) Prepare for sputtering: Start the vacuum pump and evacuate the sputtering chamber to the working vacuum degree, which is 10 -9 Pa, introduce argon gas into the sputtering chamber, the argon gas flow rate is 30sccm, install a rare earth microalloyed copper target, the rare earth microalloyed copper target contains rare earth elements lanthanum and cerium, the ratio of La to Ce is 6 / 4, the content is 1000ppm, and the content of other impurities is ≤10ppm, set the power of the sputtering power supply to 300W, adjust the distance between the target and the substrate to 8cm, and set the pre-sputtering time to 7 minutes; (4) Sputtering: Start the sputtering power supply to carry out deposition. After completion, a deposited metal substrate is obtained. (5) Annealing: The deposited metal substrate is annealed under argon gas at a temperature of 250°C for 25 minutes to obtain a rare earth micro-alloyed ultra-thin copper foil prepared by magnetron sputtering.

[0013] Embodiment 4: A rare earth micro-alloyed ultra-thin copper foil prepared by magnetron sputtering comprises the following steps: (1) Pretreatment: Place the rolled copper foil in an ultrasonic cleaning machine and immerse it in an acetone solution for cleaning for 15 minutes. After cleaning, rinse it with deionized water and place it in an oven for drying at 80°C for 60 minutes to obtain a clean metal substrate. (2) Polishing: Place the clean metal substrate into a polishing solution, which is a mixture of sulfuric acid and hydrogen peroxide. The concentration of sulfuric acid is 20%, the concentration of hydrogen peroxide is 20%, and the volume ratio of hydrofluoric acid to nitric acid is 1:1. The polishing time is 4 minutes and the polishing temperature is 50°C. After the polishing is completed, rinse with deionized water and place in an oven for drying. The oven drying temperature is 80°C and the drying time is 60 minutes to obtain a polished metal substrate. (3) Prepare for sputtering: Start the vacuum pump and evacuate the sputtering chamber to the working vacuum degree, which is 10 -9Pa, introduce argon gas into the sputtering chamber, the argon gas flow rate is 30sccm, install a rare earth microalloyed copper target, the rare earth microalloyed copper target contains rare earth elements lanthanum and cerium, the ratio of La to Ce is 6 / 4, the content is 1000ppm, the content of other impurities is ≤10ppm, set the power of the sputtering power supply to 300W, adjust the distance between the target and the substrate to 10cm, and set the pre-sputtering time to 10 minutes; (4) Sputtering: Start the sputtering power supply to carry out deposition. After completion, a deposited metal substrate is obtained. (5) Annealing: The deposited metal substrate is annealed in argon gas at a temperature of 300°C for 30 minutes to obtain a rare earth micro-alloyed ultra-thin copper foil prepared by magnetron sputtering.

[0014] Comparative Example 1: Comparative Example 1 Compared with Example 4, in the preparation process of the rare earth micro-alloyed ultra-thin copper foil in Comparative Example 1, no rare earth element is added, and other conditions remain unchanged.

[0015] Comparative Example 2: Comparative Example 2 Compared with Example 4, in the preparation process of the rare earth micro-alloyed ultra-thin copper foil in Comparative Example 2, no annealing treatment is performed, and other conditions remain unchanged.

[0016] Experimental example: According to GB / T 29847-2013, the rare earth microalloyed ultra-thin copper foil samples prepared in Examples 1-4 and Comparative Examples 1-2 were subjected to the following performance tests: Table 1 Group Tensile strength (MPa) Peel strength (N / cm) Example 1 287 2.08 Example 2 296 2.15 Example 3 315 2.28 Example 4 325 2.49 Comparative Example 1 106 1.31 Comparative Example 2 194 1.40 According to the test results in Table 1, the rare earth microalloyed ultra-thin copper foil prepared in Examples 1-4 of the present invention has good tensile strength and peel strength. By comparing Comparative Examples 1-2 with Examples 1-4, it can be seen that adding rare earth elements and performing annealing can enhance the tensile strength and peel strength of the rare earth microalloyed ultra-thin copper foil.

[0017] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

[0018] The preferred embodiments of the present invention disclosed above are only used to help explain the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to only specific implementation methods. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.

Claims

1. A rare earth microalloyed ultra-thin copper foil prepared by magnetron sputtering, characterized in that: The following steps are involved: (1) Pretreatment: Place the metal substrate in an ultrasonic cleaning machine and immerse it in an acetone solution for cleaning. After cleaning, rinse it with deionized water and place it in an oven for drying to obtain a clean metal substrate. (2) Polishing: Place the clean metal substrate in the polishing liquid, set the polishing time and polishing temperature, and after completion, rinse it with deionized water and place it in an oven to dry to obtain a polished metal substrate; (3) Prepare for sputtering: start the vacuum pump, evacuate the sputtering chamber to the working vacuum degree, introduce argon gas into the sputtering chamber, install the rare earth microalloy copper target, set the power of the sputtering power supply, adjust the distance between the target and the substrate, and set the pre-sputtering time; (4) Sputtering: Start the sputtering power supply to carry out deposition. After completion, a deposited metal substrate is obtained. (5) Annealing: The deposited metal substrate is annealed under argon gas to obtain a rare earth micro-alloyed ultra-thin copper foil prepared by magnetron sputtering.

2. The rare earth micro-alloyed ultra-thin copper foil prepared by magnetron sputtering according to claim 1, characterized in that: In step (1), the metal substrate is one of stainless steel strip, aluminum foil and rolled copper foil, the cleaning time is 10-15 minutes, the oven drying temperature is 60-80° C., and the drying time is 30-60 minutes.

3. The rare earth micro-alloyed ultra-thin copper foil prepared by magnetron sputtering according to claim 1, characterized in that: In step (2), when the metal substrate is a stainless steel strip, the polishing liquid is a mixture of nitric acid and phosphoric acid, the concentration of nitric acid is 10-15%, the concentration of phosphoric acid is 10-15%, the volume ratio of nitric acid to phosphoric acid is 1:1, the polishing time is 5-10 minutes, and the polishing temperature is 50-60°C.

4. The rare earth micro-alloyed ultra-thin copper foil prepared by magnetron sputtering according to claim 1, characterized in that: In step (2), when the metal substrate is aluminum foil, the polishing liquid is a mixture of hydrofluoric acid and nitric acid, the concentration of hydrofluoric acid is 5-10%, the concentration of nitric acid is 5-10%, the volume ratio of hydrofluoric acid to nitric acid is 1:2, the polishing time is 3-5 minutes, and the polishing temperature is 30-40°C.

5. The rare earth micro-alloyed ultra-thin copper foil prepared by magnetron sputtering according to claim 1, characterized in that: In step (2), when the metal substrate is a rolled copper foil, the polishing liquid is a mixture of sulfuric acid and hydrogen peroxide, the concentration of sulfuric acid is 15-20%, the concentration of hydrogen peroxide is 15-20%, the volume ratio of hydrofluoric acid to nitric acid is 1:1, the polishing time is 2-4 minutes, the polishing temperature is 40-50°C, the oven drying temperature is 60-80°C, and the drying time is 30-60min.

6. The rare earth micro-alloyed ultra-thin copper foil prepared by magnetron sputtering according to claim 1, characterized in that: The working vacuum degree in step (3) is 10 -6 -10 -9 Pa, and the argon gas flow rate is 20-30 sccm.

7. The rare earth micro-alloyed ultra-thin copper foil prepared by magnetron sputtering according to claim 1, characterized in that: In step (3), the rare earth microalloyed copper target contains rare earth elements lanthanum and cerium, the ratio of La to Ce is 3 / 7-6 / 4, the content is 10-1000 ppm, the content of other impurities is ≤10 ppm, the power of the sputtering power supply is 100-300 W, the distance between the target and the substrate is 5-10 cm, and the pre-sputtering time is 5-10 minutes.

8. The rare earth micro-alloyed ultra-thin copper foil prepared by magnetron sputtering according to claim 1, characterized in that: In step (5), the annealing temperature is 200-300°C, the annealing time is 10-30 minutes, and the thickness of the copper foil is 0.5-4.5 μm.